(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article provides information on the origin, signs, causes and symptoms of bronchitis, as well as the types of bronchitis. In addition, the benefits of bronchitis treatment, bronchitis therapy and bronchitis therapy, methods that prevent today’s disease are mentioned.